2005
DOI: 10.1007/s11661-005-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain and strain rate on the bauschinger effect response of three different steels

Abstract: The Bauschinger behavior after a strain reversal was evaluated for samples with microstructures representative of production sheets for a low-carbon (LC) steel, a high-strength low-alloy (HSLA) steel, and a dual-phase (DP) steel. The microstructures were produced in the samples by laboratory hot rolling and heat treatment. Bauschinger tests were run at strain rates of 0.0001, 0.001, and 0.01 s Ϫ1 , with tensile prestrains between 1 and 7 pct. After the reversal, the samples were strained 2 pct in compression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 10 publications
0
25
0
2
Order By: Relevance
“…) is calculated from the following equation [6]. So, the ratio of the Bauschinger effect decreases the rate of the yield point, and is an evaluation indicator in which back stress is made dimensionless by the mechanical property.…”
Section: Bauschinger Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…) is calculated from the following equation [6]. So, the ratio of the Bauschinger effect decreases the rate of the yield point, and is an evaluation indicator in which back stress is made dimensionless by the mechanical property.…”
Section: Bauschinger Effectmentioning
confidence: 99%
“…With regard to Dual Phase steels, many data on the Bauschinger effect has been reported [4,5], while the dependency of strain rate on the effect has been reported in the condition of strain rate from 0.001 to 0.01/s only [6], which has not been clarified in higher strain rates.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Recent research has shown a Bauschinger effect dependence on microalloying element particles [9] and dislocation structure: [10] with an increase in particle volume fraction and dislocation density, the yield stress drop in the direction of reverse strain increases. To predict the strength change, in practice, one needs a quantitative model of dislocation-particle interaction influence on the yield stress.…”
Section: Introductionmentioning
confidence: 99%
“…Particle chemistry, size and distribution should be considered to describe the influence of precipitates on the Bauschinger effect. Han [22] found that Bauschinger effect increases with pre-strain. He quantitated Bauschinger effect as with as the yield strength in compression and as the stress around which the cyclic stress-strain curve is reversed.…”
Section: B Orowan Theorymentioning
confidence: 99%